Performance evaluation of PVM with water filters and infrared reflective glass covers - Baradey, Yehya A.A (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Photovoltaic (PV) system is a device that converts solar radiation directly to electricity. The efficiency of the PV system depends on its operating temperature. The PV system converts only a selected band (from 0.35 to 0.82 μm) of solar radiation to electricity. The absorption of radiation outside this band leads to a temperature raise of PV module which affects its performance. This research aims to study the performance of poly-crystalline photovoltaic module (PC-PVM) with different thickness of water filter panels, and different types of infrared reflective pigments. Each type of pigment was coated on 3mm transparent glass layers with specific thickness in order to prevent infrared radiation to be incident on the PC-PVM by reflecting it and, therefore, to reduce the module's operating temperature, increase the output power, and increase the lifetime of the module. Three thickness of water filter panels (5mm, 10 mm, and 20 mm) were also used to absorb ultraviolet and a portion of infrared radiations which contribute to heating of PV panel. The results of the experiments showed that the optimum water filter panel was the one with thickness 10 mm. It led to about 4% improvement in the open circuit voltage of the module, and a significant reduction in the module's average operating temperature up to 21 oC. It also showed that up to 3% increment in the efficiency of the photovoltaic module was achieved due to transparent 3mm glass cover. The optimum coated cover glass was 10 micron IRR glass cover which led to about 22 oC reduction in the average operating temperature of the module, and 5.3% improvement in its open circuit voltage.